Comparison of the effect of individual saturated and unsaturated fatty acids on cell growth and death induction in the human pancreatic beta-cell line NES2Y - Fürstova, Vlasta; Kopska, Tereza; James, Roger F L; Kovar, Jan (Life sciences, 2008)
We tested the effects of various types of fatty acids, differing in the degree of saturation and in the cis/trans configuration of the double bond, on the growth and viability of NES2Y cells (a human pancreatic beta-cell line). We found that during a 48-hour incubation period, saturated fatty acids, i.e. palmitic and stearic acids, at a physiologically relevant concentration of 1 mM and higher concentrations induced death of the beta-cells while their counterpart unsaturated fatty acids, i.e. palmitoleic and oleic acids, did not induce cell death at concentrations up to 3 mM. We also found that unsaturated elaidic acid with a trans double bond exerted significant inhibition of growth of the beta-cells at a concentration approximately ten times lower, i.e. 0.1 mM vs. 1 mM, than counterpart oleic acid with a cis double bond. This is the first direct evidence that a trans unsaturated fatty acid is significantly more effective in inhibiting beta-cell growth than a counterpart cis unsaturated fatty acid. Furthermore, we newly demonstrated that beta-cell death induced by saturated fatty acids is related to significant increase of caspase-2 activity (2 to 5-fold increase) but not to caspase-3 activation. The growth-inhibiting effect of saturated fatty acids at concentrations lower than death-inducing concentrations correlates with certain increase of caspase-2 activity.
Keywords: kaspasa 3; proliferace buněk; mastné kyseliny; vztah mezi dávkou a účinkem léčiva; buněčné linie; kaspasa 2; Fatty Acids; Structure-Activity Relationship; beta-buňky; lidé; Stereoisomerism; stereoizomerie; Fatty Acids, Unsaturated; kultivační média bez séra; Cell Line; Caspase 2; Culture Media, Serum-Free; Dose-Response Relationship, Drug; nenasycené mastné kyseliny; Insulin-Secreting Cells; Cell Proliferation; vztahy mezi strukturou a aktivitou; Caspase 3; buněčné kultury; Cell Survival; Cell Culture Techniques; viabilita buněk; Humans